2017
DOI: 10.1111/jcap.12194
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a culture of practice development in an acute adolescent inpatient mental health unit

Abstract: A planned, structured, and inclusive practice development programhas transformed the nursing culture and vastly improved the care provided to adolescents presenting in acute states of distress to this mental health unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similarly to Winnicott's holding environment , clinicians clinicians in this study found that an environment conducive to containment was a pivotal feature of an inpatient model of care. The importance of the inpatient environment has been established in previous studies (Biering & Jensen, ; Delaney, ; Vella, Page, Edwards, & Wand, ). In the current study, clinicians focused on “consistency” and “transparency” as critical professional attributes.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly to Winnicott's holding environment , clinicians clinicians in this study found that an environment conducive to containment was a pivotal feature of an inpatient model of care. The importance of the inpatient environment has been established in previous studies (Biering & Jensen, ; Delaney, ; Vella, Page, Edwards, & Wand, ). In the current study, clinicians focused on “consistency” and “transparency” as critical professional attributes.…”
Section: Discussionmentioning
confidence: 81%
“…The culture of any organization is crucial to how it operates and functions (Davis & Cates, ; Garcia et al, ). Studies of adolescent inpatient units have focused on the importance of culture models in improving quality of care (Hallman, O'Connor, Hasenau, & Brady, ; Slemon, Jenkins, & Bungay, ; Vella et al, ). Regan et al () reported that to create a therapeutic milieu, a philosophy of care needs to be established to guide the culture and structure of the unit.…”
Section: Discussionmentioning
confidence: 99%
“…Within child psychiatric inpatient units, patients spend many hours of their day under the care of nurses, yet many nurses do not have formal training in evidence‐based psychological approaches such as CBT (Vella et al, 2017). At present, there is limited research regarding CBT educational models specifically designed to train nurses in child psychiatric inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…As units work toward a vision of how they expect children to be treated, there are several unit culture models to choose from; certainly, trauma informed care has become a popular organizing principle. Vella, Page, Edwards, and Wand () present their unit's adoption of Barker's Tidal Model. They explain in rich detail both the essence of the Tidal Model and how their unit implemented and sustained this philosophy of care.…”
mentioning
confidence: 99%